International trade in services - MELNYCHUK Оксана (Ius Modernum, 2020)
Background. The service sector is key to economic growth, competitiveness and improving the well-being of the population. New perceptions of the role of services have led to the realization that internal efficiency in services is important both in a particular industry sector and in all economies that are developed and developing. Opening up the services sector has the potential to bring great benefits and deserves more attention. The aim of the article is to determine the features and main trends in the development of international trade in services in modern conditions. Materials and methods. The research uses methods of analysis and synthesis, scientific generalization and comparison of data from scientific sources. Results. The article identifies the features and characteristics of the service sector over the past decade. The dynamics of international trade in services by geographical structure and types of development of countries on the basis of statistical data of international organizations is studied. It is noted that international trade in services is becoming an increasingly important part of global commerce. Aspects of the impact of the trade war on the provision of services are considered. Further prospects for the development of trade in services in the current conditions of globalization and internationalization of markets are outlined. Conclusion. The value of the world export of services has almost doubled in last ten years, and in 2019 amounted to 6.144 billion dollars. The increase in exports of services in 2018 has become a global trend. The development of international trade in services is a necessary condition for the development of the entire economy of any country in the world.